Keanekaragaman Jenis Kupu-kupu (Rhopalocera) di Sekitar Kawasan Air Terjun Sarasah Gasang Agam, Kabupaten Agam, Sumatera Barat - Azhari, Radif; satria, Rijal (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Abstract Research on butterflies (Ropalocera) around the Sarasah Gaasang Agam Waterfall Area located in Agam Regency of West Sumatra was conducted in October to December 2021. The method used is the direct capture method. The data obtained is that there are 20 species that belong to 4 families namely Nymphalidae, Pieridae, Lycaenidae, Papilionidae. Sarasah Gasang Waterfall area has a rhopalocera type diversity index (H'= 2.74) classified as moderate and the dominance index is relatively low, which is D 0.08 which means there are species that dominate. The most common species are Junonia atlites, Phaedyma columella and Eurema hecabe. Keywords Diversity of types, butterflies, Rhopalocera, sarasah gasang Agam